Poverty and Political Instability: A Bibliometric Analysis - Rassanjani, Saddam; Dahlawi, Dahlawi; Rahmi, Isramatur (Universitas Riau Kepulauan, 2026)
Poverty and political instability are two fundamental issues that continue to shape governance and public policy in many countries, particularly in the Global South. Despite the rapid growth of the literature on these issues, studies that systematically map conceptual relationships, research trends, and global knowledge structures remain limited. Existing research often treats poverty and political instability as separate or loosely connected phenomena, thereby overlooking the institutional and political mechanisms that link them. This article addresses this gap by examining how global research has constructed the relationship between poverty and political instability, with particular attention to the Global South. The study employs a bibliometric approach, analysing 706 Scopus-indexed publications from 2016 to 2025 using VOSviewer. The findings indicate a significant increase in academic attention since 2019 and reveal that poverty is predominantly framed in relation to governance, public policy, and health, while its direct linkage to political instability remains comparatively underexplored. The analysis also highlights persistent geographic disparities in knowledge production, with the Global North dominating publication networks despite increasing contributions from the Global South. These findings contribute to the literature by clarifying the structural positioning of poverty within contemporary governance debates and by identifying gaps in the empirical examination of political instability. However, this study is limited by its reliance on a single database (Scopus) and the constraints of bibliometric analysis in capturing contextual and causal dynamics. Overall, the study underscores the need for more integrative and context-sensitive approaches to understanding the relationship between poverty and political instability in the Global South.